The guru of joy : Sri Sri Ravi Shankar & the art of living - Gautier, Francois, 1950- (New Delhi : Hay House, 2002)
Biography of Sri Sri Ravi Shankar, Hindu spiritual leader.
Keywords: Shankar, Ravi, -- Sri Sri, -- 1956-; Religious leaders -- India -- Biography